Yoga and Mental Health: The Benefits of Yoga on Stress and Anxiety in Adults - S., Saran.; Hari, (International Journal of Psychosocial Rehabilitation, 2020)
All forms of exercise can improve our mood by reducing stress hormone levels, increasing the synthesis of feel-good chemicals called endorphins, and increasing the amount of oxygenated blood in our brains. Yoga, on the other hand, may provide extra advantages. It can improve mood by increasing levels of gamma-aminobutyric acid (GABA), a brain chemical linked to a better mood and less anxiety. Meditation also lowers activity in the limbic system, which is responsible for emotions. When faced with stressful situations, you have a more tempered response as your emotional reactivity declines. Depression and anxiety have traditionally been treated with drugs and talk therapy. But complementary approaches, such as yoga, also help, and yoga stacks up well when compared with other complementary therapies.Yoga has been reported to aid with post-traumatic stress disorder in several minor trials (PTSD). It is used in conjunction with other treatments to assist lessen intrusive memories and emotional reactivity, as well as generate calmer, more consistent breathing. Because it activates the parasympathetic nervous system, deep, steady breathing is linked to calmer states. This research article summarizes the current evidence on the effects of yoga interventions on various components of mental and physical health, by focusing on the evidence described in review articles. By focusing on the evidence reported in review articles, this research article summaries the current evidence on the effects of yoga therapies on several components of mental and physical health. Overall, these studies point to several areas where yoga could be useful, although further research is needed in almost all of them to prove such advantages. Metanalysis has been limited by the variability of therapies and conditions evaluated, making it an ineffective tool for summarizing the present knowledge.